2018
DOI: 10.5500/wjt.v8.i3.75
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative glucose management and outcomes in liver transplant recipients: A qualitative systematic review

Abstract: AIMTo investigate the relationship between post-liver transplantation (LT) glycemic control and LT outcomes.METHODSA qualitative systematic review on relevant prospective interventions designed to control glucose levels including insulin protocols. Studies investigating an association between glycemic control and post-LT outcomes such as mortality, graft rejection, and infection rate were reviewed. PubMed, EMBASE, and other databases were searched through October 2016.RESULTSThree thousands, six hundreds and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have reported worse survival outcomes for diabetic patients post‐LT presumably due to higher rates of infections, chronic rejections, and late onset hepatic artery thrombosis . A qualitative systematic review of perioperative glucose control also confirmed worse transplant outcomes associated with hyperglycemia . Our results demonstrated higher rates of graft rejection among PTDM individuals with trends toward worse overall survival also suggesting a unique relationship between glucose dysregulation, graft viability, and patient survival.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have reported worse survival outcomes for diabetic patients post‐LT presumably due to higher rates of infections, chronic rejections, and late onset hepatic artery thrombosis . A qualitative systematic review of perioperative glucose control also confirmed worse transplant outcomes associated with hyperglycemia . Our results demonstrated higher rates of graft rejection among PTDM individuals with trends toward worse overall survival also suggesting a unique relationship between glucose dysregulation, graft viability, and patient survival.…”
Section: Discussionsupporting
confidence: 78%
“…Some guidelines and studies recommend maintaining blood glucose below 200 mg/dL in the perioperative period between surgical procedures, including liver transplantation. 2,12 However, other targets for glucose maintenance have been suggested: 150 to 200 mg/dL by the World Health Organization, 15 150 mg/dL by Paka et al, 16 and 140 to 180 mg/dL in the guideline proposed by the American Association of Clinical Endocrinologists and the American Diabetes Association. 17 A review of the literature, concurrent with the guidelines, suggests that further studies evaluating the optimal glycemic value that may act as a protective factor against SSI in liver transplant recipients in the perioperative period are required.…”
Section: Discussionmentioning
confidence: 99%
“…Posttransplant hyperglycemia has been associated with an increased risk of ACR as well as other comorbidities. ( 46 ) In addition, hyperglycemia management after LT uses significant resources ( 47 ) and can result in additional laboratory testing, office and emergency room visits, and hospital admissions. Improvement in glycemic control after LT can result in better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%